THE LEARNING OUTCOMES OF PHYSICAL EDUCATION STUDENTS ACCORDING TO THAI QUALIFICATIONS FRAMEWORK IN ONLINE LEARNING FOR HIGHER EDUCATION, THAILAND NATIONAL SPORTS UNIVERSITY - Arunmek, Wisanu; Sanjan, Worapon (Academic Journal of Thailand National Sports University, 2023)
The purposes of this research are to study and to compare the opinions on student learning outcomes according to Thailand National Higher Education Qualifications Framework, through online study of students in the Bachelor of Education Program in Physical Education, Thailand National Sports University. The population of this research was 7,803 students majoring in Physical Education at the Faculty of Education, Thailand National Sports University, Academic Year 2022: and 384 samples from 17 campuses across the country were obtained by using a simple random sampling method, 2 campuses per region, totaling 8 campuses in all regions and set the sample proportion equally to get 48 students per campus. The instrument for collecting data is a questionnaire consisting of 6 areas, specifically: 1) morality and ethics 2) knowledge 3) cognitive skills 4) interpersonal skills and responsibility 5) numerical analysis, communication and information technology skills and 6) learning management skills. The data were analyzed to calculate frequency, percentage, mean, standard deviation using both one-way ANOVA and Scheffe methods. Results indicated as follows: 1) The opinions on learning outcomes according to the National Qualifications Framework for Higher Education in the online learning of students in the Bachelor of Education Program in Physical Education, Thailand National Sports University, are in each and every aspect of the 6 qualitative levels, at a high level of satisfaction and learning outcomes; 2) The opinions on learning outcomes according to the National Qualifications Framework for Higher Education in online learning among students in Bachelor of Education Program in Physical Education, Thailand National Sports University among campuses in specifically the North and Northeast part of Thailand differ significantly from the Central Region at the .05 level.